Technological transition and market structure: The switch-off and local television in Italy. (1st June 2022) - Mangani, Andrea; Pacini, Barbara
Media scholars raised several concerns about the digital television transition implemented at the beginning of this millennium. The impact of the transition on local TV systems is a crucial issue, because many small- and medium-sized enterprises may not be prepared to switch to a new technology and may exit the market. This article studies the survival of local TV stations in Italy during the transition to digital television. The empirical analysis shows that the adoption of the digital system is associated with a sharp decrease of the probability of survival of local TV broadcasters. While this result confirms that local media struggle to compete in the digital world, the overall assessment at the national level is not straightforward, given the imbalance between many local TV stations and scarce economic resources before the switch-off.